PENINGKATAN KEMAMPUAN BERBICARA BERBASIS PRODUKTIVITAS MELALUI SCHEDULE TEXT PADA MAHASISWA FBP UNIVERSITAS TRIATMA MULYA BALI - Ni Wayan Mekarini (Universitas Triatma Mulya, 2022)
This research take on focus the Speaking ability on producing sentences with schedule text as the basic material on first semester students on hospitality program. Research showed that effort to improve students’ speaking skill which is based on productivity can be used schedule text as the trigger. The steps can be divided into 3 such as introducing relevant vocabulary where vocabulary showed in matching column in similar number, inserting small text which support the topic and the core activity is producing sentences. The sentences produced are classified into 3 groups according to how tight the dependency to the text provided. The research found out that (a) all students produce minimal 5 sentences and even far more. No students left in achieve this type of sentences. The sentences are produces by linked information on a certain line. (b) A number of students faced it difficult to produce sentences type 2 since it needs more focus in comparing data from the schedule text. Only 85% student got it easy while the others need more time to produce one. The sentences here produced by doing comparison or linking between lines information. (c) For group 3 where sentences need knowledge background to support it is achieved by 55% students. Here, sentences produced by implementing intratext which means another text must be there so the sentences become larger or deeper than the data on schedule text itself. It seemed that not each student has enough knowledge about airlines or small text which is provided before the core activity is neglected. Lack of knowledge or effort made it difficult for some students, but still very essay for others. They can produce many sentences in this group in a minute. From the results, it is suggested for students to do reading activity on interesting topic or article supporting the learning process.